PENDIDIKAN AGAMA ISLAM DI SEKOLAH UMUM - Zakiah Al Munawarah; Muzakkir; Hasyim Haddade (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Islamic religious education is essentially a continuous effort to convey information, values ??and religious culture so that these ideals can become standards of behavior, attitudes and thought patterns and become a source of inspiration and ideals. Meanwhile, there is a strong will among the Indonesian people to always return to Pancasila and the 1945 Constitution consistently and purely. These findings suggest that religious life, and religious education in particular, is becoming increasingly important in government structures and organizations. This research uses the literature study method. The aim of this research is to: (1) examine the history of development (PAI) in public schools (2) examine the curriculum (PAI) in public schools (3) obstacles and solutions (PAI) in public schools (4) Religious Education Class Hours in Public Schools (5) Islamic Religious Education in the Context of Independent Learning.